AUTONOMOUS MOBILE ROBOT VISION BASED SYSTEM: HUMAN DETECTION BY COLOR - Mohd Shah, Hairol Nizam; Ab Rashid, Mohd Zamzuri; Mohd Sobran, Nur Maisarah (Little Lion Scientific Islamabad Pakistan, 2013)
This project related to develop and implementation of autonomous vision based mobile robot following human based on clothes color. There have two part are involve which is mobile robot platform and classification algorithms by color. The core of the classification of color are comprise into two process; offline and online. An offline process consists of the training of the static image, using deference input sources that depend on the application. An online process consists of the matching process and the result of the clothes color position. Then classification algorithm is applied to find the centroid of the human. This centroid is then compared with the center of the image to get the location of the human with respect to the camera, either at the left or right of the camera. If the human is not in the center of the camera view, then corrective measures is taken so that the human will be in the center of the camera view. Data for the centroid of human is shown through the Graphical User Interface (GUI). One of the unique advantages in this project, the detection of human by color only uses image processing that generated by the algorithms itself without additional sensor like sonar or IF sensor.